Gontor as the Learning Contemporary Islamic Institution Transformation Toward the Modernity - Fasa, Muhammad Iqbal (State Institute of Islamic Studies (IAIN) Palu, 2017)
Darussalam gontor modern islamic boarding school is one that is very instrumental in indonesia education coloring even southeast asia. the whole potential and capability to realize the mission of shed. There are five philosophical education of darussalam gontor modern islamic institution: the vision; the missions; the mottoes; the five spirits; and the long-term plan. This research attempts to offer darussalam gontor modern islamic institution transformation toward the modernity includes several things, first, based on total quality control second, based on cadre recruitment; third, based on teaching 24 hours